2021
DOI: 10.1155/2021/2262913
|View full text |Cite
|
Sign up to set email alerts
|

Anxiogenic Potential of Experimental Sleep Fragmentation Is Duration‐Dependent and Mediated via Oxidative Stress State

Abstract: Sleep architecture alterations, among which sleep fragmentation is highly prevalent, represent risk factors for a variety of diseases, ranging from cardiovascular to brain disorders, including anxiety. What mediates anxiety occurrence upon sleep fragmentation is still a matter of debate. We hypothesized that the sleep fragmentation effects on anxiety are dependent on its duration and mediated by increased oxidative stress and alterations in the number of parvalbumin (PV+) interneurons in the hippocampus. Sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…In the literature there is a discrepancy about the effect of sleep disorders or IH on the motor activity of mice. Some studies have shown similar results to current findings ( Andersen et al, 2005 ; Araujo et al, 2006 ; Meng et al, 2020 ; Onaolapo et al, 2016 ), while others found a modulation of locomotion ( Baitharu et al, 2013 ; Grubac et al, 2019 ; Grubač et al, 2021 ; Yuan et al, 2015 ). The method of fragmentation used in those studies consisted of a treadmill forced locomotion, which can induce per se a reduction in motor activity, and as such the effect may not be attributable to SF.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the literature there is a discrepancy about the effect of sleep disorders or IH on the motor activity of mice. Some studies have shown similar results to current findings ( Andersen et al, 2005 ; Araujo et al, 2006 ; Meng et al, 2020 ; Onaolapo et al, 2016 ), while others found a modulation of locomotion ( Baitharu et al, 2013 ; Grubac et al, 2019 ; Grubač et al, 2021 ; Yuan et al, 2015 ). The method of fragmentation used in those studies consisted of a treadmill forced locomotion, which can induce per se a reduction in motor activity, and as such the effect may not be attributable to SF.…”
Section: Discussionsupporting
confidence: 87%
“…As such, future exploration of the temporal trajectories of the performance in each of the cognitive and behavioral tests used herein in the context of SF may uncover heretofore unknown patterns of response. We should remark that sleep deprivation induced by different methods ( Patti et al, 2010 ; Pokk and Väli, 2002 ; Suchecki et al, 2002 ; Tai et al, 2020 ; Yaoita et al, 2020 ) can lead to different alterations in sleep architecture and basal anxiety levels of mice along with evidence of oxidative stress in the brain ( Grubac et al, 2019 ; Grubač et al, 2021 ; Nair et al, 2011a ; Tartar et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…While GSH levels did not differ between PPCS and controls, GSH showed significant positive association with functional impact of headache and daytime sleepiness, although the relationship with sleepiness was not significant after correction for multiple comparisons. Oxidative stress has been linked to various headache disorders, including migraine, that share features with post-traumatic headache ( Geyik et al, 2016 , Ashina et al, 2019 , Capi et al, 2020 ) and is often implicated in pre-clinical models of sleep disruption ( Villafuerte et al, 2015 , Hill et al, 2018 , Grubač et al, 2021 ). We suggest that PPCS symptoms such as headache are related to oxidative stress such that more symptomatic PPCS patients have higher GSH while noting that oxidative stress is not unique to mTBI ( Ghezzi et al, 2018 ) thus levels are still within normal GSH ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Negative stress causes anxiety or withdrawal (depression and anxiety), and is accompanied by unpleasant feelings, reduced work ability leading to mental and physical illnesses (32). Recent studies indicated that anxiety-related behavior in rats can also been enhanced by a lack of sleep and sleep deprivation, which can be considered as stress (33,34). Besides, it has been showed that sleep deprivation can even make brain more susceptible to seizures by changing brain production of interleukins (35).…”
Section: Positive (Eustress) and Negative (Distress) Stressmentioning
confidence: 99%